Beneficial Effect of Fluoxetine and Sertraline on Chronic Stress-Induced Tumor Growth and Cell Dissemination in a Mouse Model of Lymphoma: Crucial Role of Antitumor Immunity - Di Rosso, María Emilia; Sterle, Helena Andrea; Cremaschi, Graciela Alicia; Genaro, Ana María (Frontiers in Immunology, 2018)
Clinical data and experimental studies have suggested a relationship between psychosocial factors and cancer prognosis. Both, stress effects on the immune system and on tumor biology were analyzed independently. However, there are few studies regarding the stress influence on the interplay between the immune system and tumor biology. Moreover, antidepressants have been used in patients with cancer to alleviate mood disorders. Nevertheless, there is contradictory evidence about their action on cancer prognosis. In this context, we investigated the effect of chronic stress on tumor progression taking into account both its influence on the immune system and on tumor biology. Furthermore, we analyzed the action of selective serotonin reuptake inhibitors, fluoxetine and sertraline in these effects. For this purpose, C57BL/6J mice submitted or not to a chronic stress model and treated or not with fluoxetine or sertraline, were subcutaneously inoculated with EL4 cells to develop solid tumors. Our results indicated that chronic stress leads to an increase in both tumor growth and tumor cell dissemination. The analysis of cell cycle regulatory proteins showed that stress induced an increase in the mRNA levels of cyclins A2, D1 and D3 and a decrease in mRNA levels of cell cycle inhibitors p15, p16, p21, p27, stimulating cell cycle progression. Moreover, an augment of mRNA levels of metalloproteases (MMP-2 and MMP-9), a decrease of inhibitors of metalloproteases mRNA levels (TIMP 1, 2 and 3) and an increase in migration ability were found in tumors from stressed animals. In addition, a significant decrease of anti-tumor immune response in animals under stress was found. Adoptive lymphoid cell transfer experiments indicated that the reduced immune response in stressed animals influenced both the tumor growth and the metastatic capacity of tumor cells. Finally, we found an important beneficious effect of fluoxetine or sertraline treatment on cancer progression. Our results emphasize the crucial role of the immune system in tumor progression under stress situations. Although a direct effect of stress and drug treatment on tumor biology could not be ruled out, the beneficial effect of fluoxetine and sertraline appears to be mainly due to a restoration of anti-tumor immune response.